Where nation-states come from : institutional change in the age of nationalism - Roeder, Philip G. (ACLS Humanities E-Book., 2007)
To date, the world can lay claim to little more than 190 sovereign independent entities recognized as nation-states, while by some estimates there may be up to eight hundred more nation-state projects underway and seven to eight thousand potential projects. Why do a few such endeavors come to fruition while most fail? Standard explanations have pointed to national awakenings, nationalist mobilizations, economic efficiency, military prowess, or intervention by the great powers.